KONSEPSI PERLINDUNGAN ANAK DARI TINDAKAN EKSPLOITASI SEKSUAL KOMERSIAL ANAK PADA HUKUM INTERNASIONAL DAN PENERAPANNYA DALAM HUKUM NASIONAL - T. Riza Zarzani N (DE LEGA LATA: JURNAL ILMU HUKUM, 2017)
The conception of child protection from various forms of crime, such as sexual exploitation that has been existed in various legal provisions and at the level of international law of the existence of children as subjects of human rights which has been manifested by the ratification of the Convention on the Rights of the Child. Indonesia has implemented child protection by issuing Laws Number 23/2002. The implementation of child protection from sexual exploitation in Indonesia is conducted through legislation, namely: ratification and establishment of rules on child protection, executive efforts by making effective law enforcement agencies such as police, KPAI establishment. Efforts to combat commercial sexual exploitation are done by synergizing between law enforcement officers, legislation and preventive efforts through education.